Subgeneric taxonomy of Dichotomius Hope, 1838 and taxonomic revision of the subgenus Cephagonus Luederwaldt 1929 (Coleoptera: Scarabaeidae) - Nunes, Rafael Vieira (2016)
Dichotomius is the richest Scarabaeinae dung beetle genus of the Western Hemisphere with approximately 190 described species separated in the following subgenera: Dichotomius s. str. Hope (74 spp), Selenocopris Burmeister (76 spp.), Cephagonus Luederwaldt (revised here, 41 spp) and Homocanthonides Luederwaldt (monotypic). The genus has a large ecological application due to its high abundance in tropical terrestrial habitats, wide distribution and ecological services provided. Given this taxonomic and ecological importance of the genus, this thesis has the aim of providing a solid nomenclatural and taxonomic basis for the ongoing taxonomic revisions and natural history (ecology) works involving Dichotomius. In the first chapter, the identity of Dichotomius (S.) bicuspis (Germar) is discussed and a revised status is proposed for Selenocopris (now acquiring the same concept proposed by Luederwaldt) and Cephagonus, which is taxonomically revised with the description of several new species. In the second chapter, we provide a historical overview of the genus and of the people working on it, followed by a catalogue of name-bearing types with detailed information on type material for the genus. Finally, in this chapter, a taxonomic key of Dichotomius is provided, separating related Neotropical subgenera, Dichotomius subgenera, species groups in the subgenera and some isolated species.